Acute kidney injury post–transcatheter aortic valve replacement. Issue 12 (18th December 2017) - Ram, Pradhum; Mezue, Kenechukwu; Pressman, Gregg; Rangaswami, Janani
Abstract : Transcatheter aortic valve replacement (TAVR) is a treatment option in high‐risk patients with severe aortic stenosis who are not surgical candidates. In light of emerging evidence, it is being increasingly performed even in intermediate‐risk patients in recent years. Patients who develop acute kidney injury (AKI) following TAVR are known to have worse outcomes. The objective of this concise review was to identify the prevalence and the impact of AKI following TAVR on patient outcomes by including the most recent literature in our search. After a thorough search on MEDLINE, Google Scholar, and PubMed, we included all literature relevant to AKI following TAVR. We found that AKI was caused by a variety of reasons, such as hemodynamic instability during rapid pacing, blood transfusion, periprocedural embolization, and use of contrast medium, to name a few. In patients who developed AKI following TAVR, 30‐day and 1‐year mortality were increased. Further, in these patients, length and cost of hospital stay were increased as well. Preventive measures such as optimal periprocedural hydration, careful contrast use, and techniques to prevent embolization during device implantation have been tried with limited success. Given that TAVR is expected to be increasingly performed, this review aimed to summarize the rapidly expanding currently available literature in an effort to reduce procedural complications and thereby improve patient outcomes.